Mekanisasi Pencetak Kue Kacang - Yang Fitri Arriyani; Husman Husman; Rio Ardiansyah; Vidian Suryani (Manutech : Jurnal Teknologi Manufaktur, 2018)
Peanut cake is one of the typical Indonesian pastries which includes the most popular cakes by Indonesian people including the people of the Province of Bangka Belitung Islands. The process of processing peanut cakes through several stages, namely the processing of peanuts, the printing of bean cake dough. The current method of printing peanut cakes is still manually using one by one as a tool to print the bean cake. The purpose of this study is to design and make a bean cake printing tool that is capable of printing 20 bean cakes in one process. The stages in making this bean cake printing device start from problem identification, planning, designing, tool making, assembling, and testing. Based on the results of the trials that have been carried out, the tool is capable of printing 20 prints in a single process and the dough is not attached to the mold.